Self-stigma in psychiatric patients--standardization of the ISMI scale - Ocisková, Marie; Praško, Ján; Kamarádová, Dana; Látalová, Klára; Kurfürst, Pavel; Dostálová, Lenka; Cinculová, Andrea; Kubínek, Radim; Mainerová, Barbora; Vrbová, Kristýna; Ticháčková, Anežka (Neuro-endocrinology letters, 2014)
OBJECTIVE: Self-stigma in psychiatric patients is an issue deserving both research and therapeutic attention. The objective of the present study was to evaluate the psychometric properties of a Czech version of the Internalized Stigma of Mental Illness (ISMI) scale assessing the levels of self-stigma in individuals with mental disorders. METHODS: It consists of 29 items classified into 5 subscales, namely alienation, stereotype endorsement, perceived discrimination, social withdrawal and stigma resistance. The study group comprised 369 patients with a mean age of 41.5±13.3 years, of whom 210 (56.6%) were females. RESULTS: The most frequent diagnosis was neurotic disorders (46.1%), followed by affective disorders (18.4%), substance use disorders (13.3%), psychotic disorders (10.8%), personality disorders (9.5%) and organic disorders (1.6%). Reliability of the scale was evaluated by internal consistency analysis (α=0.91), the split-half method (Spearman-Brown coefficient: 0.93) and test-retest at 3 weeks from the first measurement (N=17; r=0.90, p<0.05). CONCLUSION: Exploratory factor analysis of the scale was performed, its validity was verified and norms were established that were based on T-scores and sten scores for the entire scale and individual subscales. The Czech translation of the ISMI has adequate psychometric properties.
Keywords: dospělí; Female; Psychometrics; psychometrie; Stereotyping; Adult; sebepojetí; mladý dospělý; ženské pohlaví; duševní poruchy; Neurotic Disorders; Self Concept; Adolescent; Reproducibility of Results; lidé; poruchy nálady; psychotické poruchy; Aged, 80 and over; neurotické poruchy; reprodukovatelnost výsledků; stereotypizace; Male; Aged; Czech Republic; Young Adult; Psychotic Disorders; Česká republika; Substance-Related Disorders; Mental Disorders; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; poruchy spojené s užíváním psychoaktivních látek; Mood Disorders; Middle Aged; mladiství; Humans